Evaluation of the Australian Gonococcal Surveillance Programme - Samaan, Gina; Roche, Paul W; Greig, Jane E; Tapsall, John W; Australian Gonococcal Surveillance Programme (Communicable Diseases Intelligence, 2005)
The Australian Gonococcal Surveillance Programme (AGSP) is a laboratory network that monitors the susceptibility of gonococcal isolates to antibiotics used in the treatment of infection. This report evaluates and reports on the simplicity, flexibility, sensitivity, representativeness, timeliness and acceptability of the AGSP. The World Health Organization's (WHO) Questionnaire for Assessment of Antimicrobial Resistance (AMR) National Networks was used in undertaking this evaluation and we report on the questionnaire's usefulness. The evaluation revealed that the AGSP was structurally simple, acceptable, timely and that the data were actively used by the stakeholders. However, the flexibility, representativeness and sensitivity of the AGSP are challenged by the increasing use of molecular based methods to diagnose gonococcal infections, as this is reducing the number of isolates available for testing. Despite this challenge, the AGSP has been able to identify differences in the antimicrobial susceptibility of gonococcal strains circulating in metropolitan and regional communities and the data generated are used to devise or modify standard treatment regimens for gonorrhoea. The functioning of the system can be improved by better availability of data through a dedicated website. Ideally, linkage of AGSP data to notification data would ensure that the AGSP is sensitive to and representative of the changes in gonococcal resistance amongst various sub-populations, although it will increase system complexity. The WHO questionnaire was found to be useful in undertaking the evaluation of the AGSP as it was simple and well-structured. However, the questionnaire needs to be expanded to include benchmarks that guide the assessment process. Commun Dis Intell 2005;29:142–148.